Viral Etiologies and Histopathological Features of Olfactory Dysfunction: A Systematic Review - Kimia Motlagh Asghari; Nasim Kakavand; Mahdieh Taiyeb Khosroshahi; Sina Janbaz Alamdari; Shaghayegh Karami; Mehran Jaberinezhad (Health Science Reports, 2025)
ABSTRACT Background and Aim Olfactory dysfunction associated with viral infections, including the recent SARS‐CoV‐2 pandemic, has raised significant clinical interest. Understanding the viral etiologies and histopathological characteristics of permanent olfactory dysfunction is essential for optimizing diagnostic and therapeutic strategies. This systematic review aims to synthesize the available evidence on the histopathological features of viral‐induced permanent olfactory dysfunction. By focusing on direct viral damage, inflammatory responses, and vascular changes, this study seeks to elucidate the underlying mechanisms of post‐viral olfactory impairment. Methods This systematic review adhered to PRISMA guidelines and was registered in PROSPERO (CRD42024520500). Searches were conducted in PubMed, EMBASE, Scopus, Web of Science, and Google Scholar up to February 14, 2024. Inclusion criteria encompassed observational studies investigating human subjects diagnosed with permanent olfactory dysfunction attributable to viral etiologies. Two reviewers independently screened studies, extracted data using predefined forms, and assessed study quality using NOS, STROBE, and JBI tools. Results Eight studies met the inclusion criteria. Predominant viral etiologies included SARS‐CoV‐2 and common cold viruses (e.g., adenovirus). Diagnostic tools varied but commonly included clinical evaluations and validated olfactory tests. Histopathological findings revealed diverse nasal tissue alterations, such as mucosal atrophy, inflammatory infiltrates, and neuroepithelial degeneration. SARS‐CoV‐2 infections demonstrated distinctive neuroepithelial and endothelial pathology contributing to olfactory dysfunction. Conclusion Viral‐induced permanent olfactory dysfunction involves multifaceted histopathological changes, including direct viral neuroinvasion and inflammatory responses. Understanding these pathophysiological mechanisms is crucial for developing targeted interventions and managing long‐term sequelae of viral infections affecting olfaction. This systematic review, the first conducted on this topic, underscores the need for further research on viral etiologies beyond COVID‐19, as they are currently understudied.